Estimating a small scale macroeconomic model of the Jamaican economy : some preliminary results - Allen, Courtney ([Caribbean Centre for Monetary Studies] [St. Augustine]TT, 2002)
Presents some preliminary results from the estimation of a small-scale model of the Jamaican economy. Identifies an aggregate demand and a stable money demand function in a contemporary framework.